2014
DOI: 10.1152/ajpcell.00250.2014
|View full text |Cite
|
Sign up to set email alerts
|

Induction of angiotensin-converting enzyme after miR-143/145 deletion is critical for impaired smooth muscle contractility

Abstract: S. Induction of angiotensin converting enzyme after miR-143/145 deletion is critical for impaired smooth muscle contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Isometric Force Measurements-Aortic rings (1.5-2 mm in length) were mounted in a Mulvany myograph (610M, Danish Myo Technology) as described previously (31). After an equilibration period, cumulative concentration-response curves for serotonin (5-hydroxytryptamine; 5-HT) were generated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isometric Force Measurements-Aortic rings (1.5-2 mm in length) were mounted in a Mulvany myograph (610M, Danish Myo Technology) as described previously (31). After an equilibration period, cumulative concentration-response curves for serotonin (5-hydroxytryptamine; 5-HT) were generated.…”
Section: Methodsmentioning
confidence: 99%
“…The regulation of L-type calcium channel expression by miR-145 is in part mediated by direct interaction of miR-145 with its target CamKII␦ (26,66), which in turn affects the translocation of a transcriptional repressor called DREAM (67). In earlier studies, we found that knockdown of miR-145 or genetic deletion of the miR-143/145 cluster results in increased CamKII␦ expression and reduced expression of L-type calcium channels (26,31,65). Considering the sensitivity to L-type calcium channel verapamil, it is likely that reduced L-type calcium channel expression is involved in the diminished glucose-mediated transcription of contractile smooth muscle markers in miR-143/145 KO cells.…”
Section: No Diabetesmentioning
confidence: 96%
“…Most notably, the miR-143/145 cluster is essential for vascular smooth muscle contractile differentiation and vascular function [33,34,[37][38][39][44][45][46].…”
Section: Several Of the Actin/mrtf-a-sensitive Mirnas Identified In Tmentioning
confidence: 99%
“…cluster, which is known to be enriched in smooth muscle and promote contractile smooth muscle differentiation [35][36][37][38][39]. However, to our knowledge, the transcriptional regulation of miRNAs by MRTF-A and actin dynamics has not been investigated previously in vascular smooth muscle, although multiple lines of evidence points towards a crucial role of actin/MRTF in vascular disease.…”
Section: Introductionmentioning
confidence: 97%
“…miR-143 and -145 have been shown to regulate the differentiation and functions of smooth muscle cells in the vessel wall structure. An in vitro study examining vascular diseases indicated that vessel wall stress may cause lower expression of these miRNAs [34,35]. It was demonstrated that these miRNAs may be necessary for neointima formation in atherosclerosis [36].…”
Section: Micro-rnas In Cardiovascular Diseasesmentioning
confidence: 99%